Antimicrobial Peptides from Insects: An Overview - Ravi, C.; Jeyashree, A.; Renuka Devi, K. (Research in Biotechnology, 2011)
Bacteria are exceptionally adept at acquiring resistance to antibiotics and antiseptic agents, hence new antibiotics and strategies are therefore needed to deal with this threat. Several authors have reported the inhibitory effect of anti microbial peptides of animal origin on bacteria and research is on the rise about insect antimicrobial peptides. An attempt has been made to have a comprehensive review of the research work carried out on antimicrobial peptides from insects.